Brain Death and Its Entanglements: A Redefinition of Personhood for Islamic Ethics. - Haque, Omar Sultan (Journal of Religious Ethics, 2008)
The Islamic philosophical, mystical, and theological sub-traditions have each made characteristic assumptions about the human person, including an incorporation of substance dualism in distinctive manners. Advances in the brain sciences of the last half century, which include a widespread acceptance of death as the end of essential brain function, require the abandonment of dualistic notions of the human person that assert an immaterial and incorporeal soul separate from a body. In this article, I trace classical Islamic notions of death and the soul, the modern definition of death as "brain death," and some contemporary Islamic responses to this definition. I argue that a completely naturalistic account of human personhood in the Islamic tradition is the best and most viable alternative for the future. This corporeal monistic account of Muslim personhood as embodied consciousness incorporates the insights of pre-modern Muslim thinkers yet rehabilitates their characteristic mistakes and thus has the advantages of neuroscientific validity and modern relevance in trans-cultural ethical discourse; it also helps to alleviate organ shortages in countries with majority Muslim populations, a serious ethical impasse of recent years.